Unrearranged immunoglobulin variable region genes have a functional promoter. - Bentley, D L (1982)
We have tested whether immunoglobulin light chain variable region genes are capable of directing initiation of transcription without undergoing the DNA rearrangement which creates a complete immunoglobulin gene. Two human Vk genes specifically initiated transcription in vitro at a site which is approximately 30 bases downstream of a TATA box and 20 bases upstream of the initiation codon. A Vk pseudogene which lacks a TATA box at an homologous position was not transcribed to a detectable extent in the in vitro system. One of the Vk genes was injected into Xenopus oocytes and it initiated transcription at precisely the same position as in the HeLa cell extract. It is suggested that the promoter which we have identified upstream of unrearranged Vk genes operates in lymphocytes after V-J joining has occurred to initiate transcription of light chain messenger RNA.